On the History and Theory of Global Constitutionalism - Mattias Kumm (Global Constitutionalism from European and East Asian Perspectives, 2018)
Concluding the first part, Mattias Kumm retraces the history of Global Constitutionalism, explaining that narratives are very much part and parcel of the history of western legal and political thought and have been connected to periods of western hegemony. With such a historical background, can Global Constitutionalism be sufficiently civilizationally and culturally inclusive? Can it be relevant when western hegemony seems to be receding and the balance of power shifting in favour of other regions? After clarifying concepts, the chapter provides some basic ideas toward an affirmative genealogy of Global Constitutionalism. Drawing on examples from Asian and European history, it shows first that universal categories and their meaning have often been shaped by contestations between different actors, not simply dictated by "the west". It shows also that anti-constitutionalist claims, often made in the name of national tradition, culture, or sovereignty, have served as a cover for the continuation of practices of domination by national elites and as a shield for these from challenges by the oppressed. Third, the chapter shows that to the extent that international legal structures perpetuate forms of domination, constitutionalism has demonstrated the internal resources to criticize these and to guide efforts of progressive development and reform.
Keywords: 300